2022
DOI: 10.15212/amm-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ginsenoside CK against oxidative stress-induced neuronal damage, assessed with 1H-NMR-based metabolomics

Abstract: Oxidative stress is an important pathogenic mechanism in degenerative diseases such as Alzheimer’s disease. Although ginsenoside compound K (CK) is protective against neuronal oxidative damage, the underlying mechanism remains to be understood. In this study, the protective effects of ginsenoside CK against oxidative stress damage induced by hydrogen peroxide in HT22 cells were investigated with 1H nuclear magnetic resonance (1H-NMR)-based metabolomics. The optimal CK concentration for decreasing oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…65 Meanwhile, the effects of ginsenoside monomers such as ginsenosides Rg1, Re, and Rc and compound K are also investigated. [66][67][68] Protopanaxadiol (PPD) and ginseng polysaccharides have better effects on energy generation and metabolism than that of protopanaxatriol (PPT). 53 However, given the opposite drug properties and the direct causality of "Shanghuo" and ginseng abuse, it is necessary to focus on the relevant effects of the ginsenosides of ginseng or red ginseng compared to ginseng leaves or American ginseng as the first group have higher contents of ginsenosides (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…65 Meanwhile, the effects of ginsenoside monomers such as ginsenosides Rg1, Re, and Rc and compound K are also investigated. [66][67][68] Protopanaxadiol (PPD) and ginseng polysaccharides have better effects on energy generation and metabolism than that of protopanaxatriol (PPT). 53 However, given the opposite drug properties and the direct causality of "Shanghuo" and ginseng abuse, it is necessary to focus on the relevant effects of the ginsenosides of ginseng or red ginseng compared to ginseng leaves or American ginseng as the first group have higher contents of ginsenosides (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…Metabonomics provide more comprehensive phenotypic characteristics and physiologic interactions of diseases. Compared with twodimensional cell culture, three-dimensional cultures more efficiently simulate the physiologic environment in vivo, thus are more suitable for combined research with metabonomics [51,52].…”
Section: Mechanism Studymentioning
confidence: 99%
“…2 Ginsenosides, the primary active ingredients in Panax ginseng, have demonstrated significant potential in treating various diseases, including cardiovascular disorders and cancers, attracting considerable attention in recent decades. 3,4 To elucidate the chemical composition of the Panax genus and discover potential lead compounds, extensive phytochemical studies have been conducted and new compounds continue to be reported. 5−7 To summarize, as of 2020, at least 573 saponin compounds (ginsenosides) were reported from the Panax genus.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Panax ginseng , one of the most renowned Chinese medicinal and edible herbs, is in high demand globally, particularly in China and Korea . Ginsenosides, the primary active ingredients in Panax ginseng , have demonstrated significant potential in treating various diseases, including cardiovascular disorders and cancers, attracting considerable attention in recent decades. , To elucidate the chemical composition of the Panax genus and discover potential lead compounds, extensive phytochemical studies have been conducted and new compounds continue to be reported. To summarize, as of 2020, at least 573 saponin compounds (ginsenosides) were reported from the Panax genus . Known ginsenosides comprise four classic sapogenins: protopanaxadiol (PPD)-type, protopanaxatriol (PPT)-type, oleanolic acid (OA)-type, and octillol (OCT)-type ginsenosides (Figure ).…”
Section: Introductionmentioning
confidence: 99%